2017
DOI: 10.1002/pmh.1394
|View full text |Cite
|
Sign up to set email alerts
|

Using the SAPAS to identify risk for personality disorders among psychiatric outpatients in India: A feasibility study

Abstract: Personality disorders (PDs) are common among psychiatric outpatients and are associated with increased morbidity and worse treatment outcomes. Epidemiological research conducted among this population in Asian countries is limited, reflecting a significant gap in the current literature. One barrier to this research is the lack of appropriate screening tools. The current research assessed the feasibility of using the SAPAS (Standardized Assessment of Personality-Abbreviated Scale) screening tool to identify indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Sampling bias might be present because of the gap of a day in conducting the tests and the six-hour data collection slot each day. Although we found a positive association between the SAPAS and IPDE measures for personality dysfunction, providing preliminary evidence of convergent validity – and previous research has established the test–retest reliability and convergent validity in a variety of psychiatric and offender populations 47,5254,56,57 – nonetheless, further reliability testing and validation of the measure in this new population is required.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Sampling bias might be present because of the gap of a day in conducting the tests and the six-hour data collection slot each day. Although we found a positive association between the SAPAS and IPDE measures for personality dysfunction, providing preliminary evidence of convergent validity – and previous research has established the test–retest reliability and convergent validity in a variety of psychiatric and offender populations 47,5254,56,57 – nonetheless, further reliability testing and validation of the measure in this new population is required.…”
Section: Discussionsupporting
confidence: 60%
“…A previous study using the SAPAS in an out-patient psychiatric setting in India had found that the SAPAS tended to over-diagnose PD with a cut-off score of 4, and had recommended translation of the SAPAS into Bengali, the local language, with evaluation of the sensitivity and specificity at different cut-off points to optimize its use. [48] This study does that, and translation of the SAPAS into Bengali undoubtedly leads to an improvement in its ability to accurately diagnose PD, as demonstrated by the improved positive predictive value compared to the previous study. It also concludes that a cut-off score of 4 does provide the best balance between sensitivity and specificity when used in an ED population.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The measure is brief, only takes approximately 2 min to complete and has also been successfully used to assess the impact of personality difficulties in large clinical samples (Gorwood et al, 2010;Mars et al, 2021). It has been tested extensively in adult populations of clinical (Bukh et al, 2010;Germans et al, 2008Germans et al, , 2012Germans et al, , 2013Gonzalez, 2014;Hesse et al, 2008;Innocent et al, 2018;Kok et al, 2017), forensic (Kongerslev et al, 2012;Shaw et al, 2012), and community samples (Bach et al, 2020;Ball et al, 2017;Fok et al, 2015), demonstrating good psychometric properties, although it appears to perform more effectively in clinical, rather than community samples (Fok et al, 2015). The SAPAS has been adapted for use in incarcerated male adolescents (Kongerslev et al, 2012) where it correctly identified 86% of participants, although the ability of this version to assess functioning was not examined.…”
mentioning
confidence: 99%